Vivien T. Thomas, the pioneering lab assistant who revolutionized congenital heart disease surgery - Natalia Ceneda; Salvatore Giordano; Giuseppe Biondi-Zoccai; Marco Bernardi (Heart Vessels and Transplantation, 2023)
Tetralogy of Fallot (ToF) is the most common cyanotic congenital heart disease. Patients who have undergone surgical repair of ToF constitute one of the largest groups of congenital heart disease patients surviving into adulthood. The history of ToF surgical techniques has evolved through the years, starting from the early 1930s. In this context, many leading figures are acknowledged as pioneers in cardiothoracic surgery. There is one who has struggled to obtain fair recognition of his work: Vivien T. Thomas. This young Afro-American man, because of his origin and economic possibilities, had to wait more than 30 years before being recognized his pivotal role in the groundbreaking first open-heart pediatric surgery of ToF.